Night Bus: a short film screenplay - Dooley, Kath (2015)
Night bus is a creative exploration of relationship between the screenplay, affect and bodies. The short film script sees a re-imagining of contemporary, real life events to produce a dramatic narrative concerned with themes of public violence, individual intervention and responsibility. Following on from research into the affective dimensions of cinema, this has been written as a means to explore the conditions that encourage the production of bodily sensation at a conscious and unconscious level within the screenplay itself. I have sought an answer to the question of how the screenwriter’s description of material gives rise to a visceral response in the reader, which may also be reflected in a resulting film text. My screenwriting focuses on the creative use of narrative content and the description of aesthetic dimensions such as colour, light, sound, movement, rhythm and texture to affect the reader.